Cultural history of death : ed by Helen MacDonald. - MacDonald, Helen; Bloomsbury (Firm) (London : Bloomsbury Academic, 2024)
"How has our understanding of death evolved over the course of 2,500 years? What can recorded history tell us about how different cultures and societies have felt about, experienced, responded to and marked the occasion of death across different periods and lands? These are the questions pursued by 54 experts in this landmark work that explores the way past societies thought, behaved and developed as they wrestled with enormity of their own mortality. The volumes draw on history, anthropology and cultural studies to carve a complete picture of death, its symbols and interpretations from Antiquity to the present day."--Publisher site.
vol. 1. In Antiquity / edited by Mario Erasmo -- vol. 2. In the Middle Ages / edited by Ashby Kinch -- vol. 3. In the Renaissance / edited by Gordon D. Raeburn and Nathaniel A. Warne -- vol. 4. In the Age of Enlightenment / edited by Jeffrey Freedman -- vol. 5. In the Age of Empire / edited by Helen MacDonald -- vol. 6. In the Modern Age / edited by Douglas J. Davies.
Includes bibliographical references and index.
Keywords: Death; Death -- History; Death -- Anthropological aspects; Death -- Social aspects